UPAYA MENINGKATKAN MOTIVASI BELAJAR MURID KELAS V SD NEGERI FATUBAI KECAMATAN INSANA TENGAH KABUPATEN TIMOR TENGAH UTARA - RONI HARIYANTO BHIDJU (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
This study aims to increase the learning motivation of fifth graders at Fatubai State Elementary School, Insana Tengah District, North Central Timor Regency, East Nusa Tenggara Province, for the 2020/2021 Academic Year. The study population used all fifth grade students of SD Negeri Fatubai, Insana Tengah District, North Central Timor Regency, East Nusa Tenggara Province, amounting to 12 people. The results of the study explain that 1) Based on the value conversion data in measuring the level of motivation, it shows that; of the number of students 12 people, 6 students have a very high level of motivation in participating in the learning process, 4 students have a good or high level of motivation and 2 students have a fairly good or high level of motivation, with an average level of motivation grade is good or high. 2) Based on the class attendance list, the level of motivation and attendance of students experienced very good results when compared to before the implementation of the actualization. 3) The idea of ??solving the issues arranged in the actualization design is able to increase the learning motivation of the fifth grade students of SDN Fatubai both the level of attendance and participation in the learning process. 4) Implementation of actualization with the idea of ??solving issues not only answers the problem of the low motivation of students to learn, but is also able to increase the awareness of parents/guardians of students towards children's education and is able to improve time discipline for students. 5) The results of actualization activities (Habituation) which are guided by the basic values ??of civil servants have become the basis for changing attitudes and behavior of the author to become a better individual, responsible, able to work together, able to innovate, responsive, caring, disciplined, and better understand the meaning the importance of coordinating not only in the workplace but also in the community and family. 6) The successful implementation of actualization can only be achieved by applying the basic values ??of civil servants and interpreting the position and role of civil servants to the fullest. ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi belajar murid kelas V SD Negeri Fatubai Kecamatan Insana Tengah Kabupaten Timor Tengah Utara Propinsi Nusa Tenggara Timur Tahun Pelajaran 2020/2021. Populasi penelitian menggunakan seluruh siswa kelas V SD Negeri Fatubai Kecamatan Insana Tengah Kabupaten Timor Tengah Utara Provinsi Nusa Tenggara Timur yang berjumlah 12 orang. Hasil penelitian menjelaskan bahwa 1) Berdasarkan data konversi nilai dalam mengukur tingkat motivasi menunjukkan bahwa; dari jumlah peserta didik 12 orang, 6 orang murid memiliki tingkat motivasi sangat tinggi dalam mengikuti proses pembelajaran, 4 orang peserta didik memiliki tingkat motivasi baik atau tinggi dan 2 orang peserta didik memiliki tingkat motivasi cukup baik atau cukup tinggi, dengan rata-rata tingkat motivasi kelas adalah baik atau tinggi. 2) Berdasarkan daftar hadir kelas, tingkat motivasi dan kehadiran peserta didik mengalami hasil yang sangat baik jika dibandingkan dengan sebelum pelaksanaan aktualisasi. 3) Gagasan pemecahan isu yang disusun dalam rancangan aktualisasi mampu meningkatkan motivasi belajar peserta didik kelas V SDN Fatubai baik tingkat kehadiran maupun partisipasi dalam proses pembelajaran. 4) Pelaksanaan aktualisasi dengan gagasan pemecahan isu tidak hanya menjawab persoalan tentang rendahnya motivasi belajara murid, tetapi juga mampu meningkatkan kepedulian orang tua/wali peserta didik terhadap pendidikan anak serta mampu meningkatkan disiplin waktu bagi peserta didik. 5) Hasil kegiatan aktualisasi (Habituasi) yang berpedoman pada nilai-nilai dasar PNS telah menjadi dasar perubahan sikap dan perilaku penulis menjadi individu yang lebih baik, bertanggung jawab, mampu bekerja sama, mampu berinovasi, responsif, peduli, disiplin, serta lebih memahami arti pentingnya berkoordinasi bukan hanya ditempat kerja tetapi juga dilingkungan masyarakat dan keluarga. 6) Keberhasilan pelaksanaan aktualisasi hanya dapat tercapai dengan menerapkan nilai-nialai dasar PNS serta memaknai kedudukan dan peran PNS secara maksimal.